Antibacterial Activity of Macrocyclic Complexes of Cu(II), Ni(II) and VO(II) Derived from o-Aminobenzaldehyde - K. Anuradha; R. Rajavel (E-Journal of Chemistry)
Novel Cu(II),Ni(II) and VO(II) complexes are synthesized with N1,N4-bis(2-aminobenzylidene)benzene-1,4-diamine (L). Complexes were characterized by elemental analysis, molar conductance, IR, UV and EPR. Spectral studies reveals a square planner geomentry for Cu(II), Ni(II) complexes and square pyramidal for VO(II) complex. The ligand and its complexes were also evaluated against the growth of gram positive bacteria and gram negative bacteria.